The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1093/her/cyy018
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of dropout in the school-based multi-component intervention, ‘Mexa-se’

Abstract: To identify the predictors of dropout in the 'Mexa-se' intervention according to the body mass index (BMI) category. This was a controlled, non-randomized study. The intervention included: (i) increase in the intensity of physical activities (PA) in physical education (PE) classes; (ii) active recess; (iii) educational sessions on PA, nutrition and body image; and (iv) educational materials. Dropout was considered when students dropped out of intervention, or did not reach 75% attendance in PE classes. The ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…The adolescents, parents and program implementers described benefits across seven main areas, including dancing and related skills, behaviours (e.g., reduced television viewing), physical well-being, psychological well-being, relationships, respect for others and for diversity, and school performance. A PA, diet and mental health intervention assessed predictors to dropout in the 'Mexa Se' intervention [79]. It was reported that in the intervention group, age, body mass, height and BMI were all significant predictors of drop out.…”
Section: Intervention Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The adolescents, parents and program implementers described benefits across seven main areas, including dancing and related skills, behaviours (e.g., reduced television viewing), physical well-being, psychological well-being, relationships, respect for others and for diversity, and school performance. A PA, diet and mental health intervention assessed predictors to dropout in the 'Mexa Se' intervention [79]. It was reported that in the intervention group, age, body mass, height and BMI were all significant predictors of drop out.…”
Section: Intervention Resultsmentioning
confidence: 99%
“…Berria et al [79] To In the crude analysis for the entire sample and among students with adequate BMI at baseline, there was a greater probability of dropping out with increasing age and BMI. Students classified as overweight were more likely to drop out with increasing age.…”
Section: Pa Diet and Mental Healthmentioning
confidence: 98%
See 3 more Smart Citations